Aktivitas Antiparkinson Ekstrak Rimpang Temulawak (Curcuma Xathorriza Roxb.) Pada Tikus Putih (Rattus Norvegicus) Galur Sprague Dawley Yang Diinduksi Haloperidol - Nofika Dwi Anitasari; Jason Merari Peranginangin; Sri Rejeki Handayani (Fakultas Farmasi Universitas Setia Budi, 2017)
Temulawak (Curcuma xathorriza Roxb.) Is a plant that contains curcumin. Curcumin in ethanol extracts of temulawak rhizome has been shown to penetrate the blood brain barrier and has a neuroprotective effect that can reduce the symptoms of parkinsonism caused by haloperidol. This study aims to determine the activity of ethanol extract of temulawak rhizome in reducing symptoms of Parkinson's and know the effective dose of temulawak rhizome extract in reducing symptoms of Parkinson's.This study used 35 rats divided into 7 groups, each group consisting of 5 rats. Group 1 was given aquadestilata. Group II was given a solution of 0.5% CMC-Na p.o. Group III was given levodopa dose 27 mg/kgbb. Group IV was given vitamin E dose of 180 IU/kgbb. Groups V, VI, VII were given the temulawak extracts of 120, 240 and 480 mg/kgbb. 45 minutes later all groups except group I were given haloperidol 2 mg/kgbb i.p. The catalepsy and rota rod tests were performed on days 0, 4, 7, 11 and 14.From catalepsy test of temulawak extract dose 120, 240, 480 mg/kgbb respectively showed activity of catalepsy decrease equal to 23,25; 52,28 and 58,56 %. While in rota rod test shows the activity increase time of latency consecutively equal to 26,87; 30,34 and 34,58 %. The effective dose of temulawak rhizome extract in reducing symptoms of Parkinson's is a dose of 240 mg / kgbb